2010
DOI: 10.1002/pola.23855
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of carbon nanotubes with pyrene‐functionalized linear‐dendritic hybrid polymers

Abstract: A series of linear-dendritic hybrid polymers, containing pyrene units at the periphery of aliphatic polyester dendrons, were prepared for the purpose of dispersing shortened single-walled carbon nanotubes (SWNTs) in tetrahydrofuran (THF). The prepared hybrids contained 1, 2, 4, 8, or 16 (G0 through G4) pyrene units and a linear segment composed of polystyrene. It was found that a minimum of four pyrene units was necessary to form a strong enough interaction with SWNTs to enable steric stabilization in solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 103 publications
(119 reference statements)
3
54
0
Order By: Relevance
“…Under the rubric of noncovalent functionalization, the strategy based on strong π‐stacking interaction between polycyclic aromatic hydrocarbon, particularly pyrene derivatives, and CNTs has been paid more attention. Since Dai and coworkers first reported that pyrenebutanoic acid succinimide ester could be physically bound on the nanotube surface,12 a great number of pyrene‐containing compounds13–19 and polymers20–28 have been synthesized for noncovalent functionalization of CNTs. In a typical work related to composite application, pyrene‐capped polystyrene was synthesized and used as an effective nanotube dispersant for preparation of polystyrene/CNT composites 22.…”
Section: Introductionmentioning
confidence: 99%
“…Under the rubric of noncovalent functionalization, the strategy based on strong π‐stacking interaction between polycyclic aromatic hydrocarbon, particularly pyrene derivatives, and CNTs has been paid more attention. Since Dai and coworkers first reported that pyrenebutanoic acid succinimide ester could be physically bound on the nanotube surface,12 a great number of pyrene‐containing compounds13–19 and polymers20–28 have been synthesized for noncovalent functionalization of CNTs. In a typical work related to composite application, pyrene‐capped polystyrene was synthesized and used as an effective nanotube dispersant for preparation of polystyrene/CNT composites 22.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of materials have been electrostatically, covalently, or hydrophobically assembled onto the CNT's surface, resulting in novel nanoconstructs and enhanced dispersion of CNTs in selected matrices. 10–16…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has a strong tendency to form excimers via intermolecular π–π stacking, which exhibit a broad and structure‐less fluorescent emission red‐shifted with respect to that of monomeric pyrene. In the past decades, several pyrene‐labeled dendrimers have been developed by a noncovalent incorporation of pyrene into the cavities of the dendrimers, or covalent attachment of pyrene to the core or periphery of the dendrimers 18–26. However, few of them have been reported for use in sensory applications 21…”
Section: Introductionmentioning
confidence: 99%